2022
DOI: 10.1371/journal.pone.0269863
|View full text |Cite
|
Sign up to set email alerts
|

Activation of plant immunity by exposure to dinitrogen pentoxide gas generated from air using plasma technology

Abstract: Reactive nitrogen species (RNS) play an important role in plant immunity as signaling factors. We previously developed a plasma technology to partially convert air molecules into dinitrogen pentoxide (N2O5), an RNS whose physiological action is poorly understood. To reveal the function of N2O5 gas in plant immunity, Arabidopsis thaliana was exposed to plasma-generated N2O5 gas once (20 s) per day for 3 days, and inoculated with Botrytis cinerea, Pseudomonas syringae pv. tomato DC3000 (Pst), or cucumber mosaic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…The signi cant induction of JA-related gene expression in the indirectly exposed leaves (Fig. 5), together with the fact of JA/ET signaling pathway activation shown in the previous study 59 , suggests that N 2 O 5 gas exposure induces an ISR-like systemic response. Some reports discuss SA/JA crosstalk, where SA-and JA-mediated signaling interact with each other antagonistically or synergistically depending on the conditions [63][64][65] .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The signi cant induction of JA-related gene expression in the indirectly exposed leaves (Fig. 5), together with the fact of JA/ET signaling pathway activation shown in the previous study 59 , suggests that N 2 O 5 gas exposure induces an ISR-like systemic response. Some reports discuss SA/JA crosstalk, where SA-and JA-mediated signaling interact with each other antagonistically or synergistically depending on the conditions [63][64][65] .…”
Section: Discussionsupporting
confidence: 65%
“…a few years ago58 , in addition to existing plasma synthesis of O 3 and NO/NO 2 from air. Furthermore, the activation effects of APP-synthesized N 2 O 5 gas on plant immunity were demonstrated through pathogen inoculation tests on N 2 O 5 -stimulated plants, indicating its potential as a new technology for the control of plant diseases59 . However, the biological mechanisms by which plants respond to dinitrogen pentoxide at a fundamental physiological level remain poorly understood.…”
mentioning
confidence: 99%
“…4 F, G). Moreover, it was recently reported that exposure of Arabidopsis thaliana to N 2 O 5 gas leads to the induction of an immune response during a pathogen inoculation test (Tsukidate et al 2022 ). This indicates that N 2 O 5 is absorbed by the surface of the plant tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, N 2 O 5 does not have the residual properties found in other chemicals. Furthermore, exposure to N 2 O 5 gas activates plant immunity and suppresses both Botrytis cinerea infection and propagation of Cucumber mosaic virus strain yellow in Arabidopsis 4 . Besides, several genes involved in jasmonic acid (JA) and ethylene signaling pathways and the synthesis of secondary metabolites from tryptophan metabolism are immediately activated by N 2 O 5 exposure in Arabidopsis 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%